2023
DOI: 10.1093/ageing/afad132
|View full text |Cite
|
Sign up to set email alerts
|

Complex interventions for improving independent living and quality of life amongst community-dwelling older adults: a systematic review and meta-analysis

Abstract: Background community-based complex interventions for older adults have a variety of names, including Comprehensive Geriatric Assessment, but often share core components such as holistic needs assessment and care planning. Objective to summarise evidence for the components and effectiveness of community-based complex interventions for improving older adults’ independent living and quality of life (QoL). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The impact of complex interventions set in primary care on older people’s outcomes has been extensively researched in recent decades. Findings from previous reviews have been mixed overall on admissions to hospital, 8 13 , 56 ARC placement, 8 10 , 12 , 13 , 18 functional ability, 8 , 9 , 12 16 and QoL. 11 14 , 18 In the present review, an intervention benefit to older people’s SRH and functional ability was found.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The impact of complex interventions set in primary care on older people’s outcomes has been extensively researched in recent decades. Findings from previous reviews have been mixed overall on admissions to hospital, 8 13 , 56 ARC placement, 8 10 , 12 , 13 , 18 functional ability, 8 , 9 , 12 16 and QoL. 11 14 , 18 In the present review, an intervention benefit to older people’s SRH and functional ability was found.…”
Section: Discussionmentioning
confidence: 45%
“…Many intervention trials set in primary care have tested the effectiveness of preventive rather than disease-specific approaches relating to the care of older people, and numerous systematic reviews related to this topic have been published. Previous reviews have found mixed effects on older people’s admissions to hospital 8 13 and aged residential care (ARC), 8 10 , 12 , 13 functional ability, 8 , 9 , 12 16 and QoL. 11 14 These reviews often report effects according to the primary intervention focus or what is thought to be its active ingredient — for example, multidimensional assessment and subsequent management; 8 , 9 , 14 , 17 health promotion and disease prevention programmes; 15 , 16 , 18 or preventive home visiting.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence shows variation in the role in different studies in terms of duration and frequency of home visits and HCPs who coordinated the care. 11 38 39 Further research needs to identify who could best coordinate care in older people and what the best approach may be.…”
Section: Discussionmentioning
confidence: 99%
“…3 9 However, the effectiveness of CGA for older people with frailty in primary care and community settings is mixed. 8 10 11 Ho et al reported benefits in terms of the likelihood of living at home, reduced mortality, improved cognition and activities of daily living, but with uncertain benefits on quality of life, 11 whereas Briggs et al found no difference in mortality, activities of daily living, quality of life and care home admissions. 8 Descriptions of CGA components often lack detail, including the delineation of staff involved in delivery, and an understanding about factors that affect implementation are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation